Design of symmetrical half-bridge converter with a series coupling capacitor. (29th June 2020) - Rashmi, Ruchi; Jagtap, Shweta
Abstract : Purpose: With the advancement of technology, size, cost, and losses of the switched mode power supply (SMPS) have been decreasing. However, due to the high frequency switching, design of magnetic drives and isolation circuits are becoming a crucial factor in SMPS. This paper presents design criteria, procedure and implementation of AC-DC half bridge (HB) converter with lower cost, smaller size and lower voltage stress on the power switch. Design/Methodology/approach: The HB converter is designed in a symmetrical mode with a series coupling capacitor. Isolated power supplies are used for the converter and control circuit. Further, a transformer based isolated gate driver is used to drive both MOSFETs. The control IC works in voltage control mode to regulate voltage by controlling the duty cycle of the MOSFETs. Findings: Control characteristics and performance of the HB converter is simulated using the MATLAB software and prototype of 170 W HB converter is built to validate the analytical results under variable load current and source voltage. The power quality and variation of load voltage at 2 A, 5 A, 7 A are reported. Originality/value: This paper presents the design of a low-cost HB converter in a symmetrical mode which saves the additional cost of symmetric correction circuit normally required in asymmetrical mode design. This paper also focuses on the selection of primary and secondary side switch, series coupling capacitor, commuting diode, isolated drive and charge equalizer resistor.